Sosialisasi Penggunaan Media Sosial Dan E- Commerce Sebagai Sarana Promosi Produk Mocaf KWT Gemilang-II - Febie Elfaladona; Meivi Kusnandar; Henny Madora; Denny Alfian; Nuril Maghfirah; Catur Bagus Satria N; Muqorrobin Hasir (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: This Community Service Program was carried out with the Gemilang II Women Farmers Group (KWT Gemilang II) to enhance digital capacity in marketing Mocaf flour products. The main problems faced by the partners were low digital literacy, the absence of a systematic marketing strategy, and limited skills in promotional content creation. The implementation method included an initial survey to map needs, preparation of training materials, digital literacy socialization, creation of social media accounts, and assistance in producing promotional content. The results showed that the partners began to understand the role of social media and e-commerce, established official promotional accounts, and were able to independently produce simple content. The conclusion of this program is that the improved digital capacity of KWT Gemilang II provides a foundation for more sustainable online-based marketing management while supporting local economic development through alternative food products. Keywords: digital marketing; entrepreneurship; KWT Gemilang II; MOCAF; UMKM Abstrak: Kegiatan Pengabdian kepada Masyarakat ini dilaksanakan bersama Kelompok Wanita Tani (KWT) Gemilang II dengan tujuan meningkatkan kapasitas digital dalam memasarkan produk tepung Mocaf. Permasalahan utama mitra adalah rendahnya literasi digital, ketiadaan strategi pemasaran yang sistematis, dan keterbatasan dalam produksi konten promosi. Metode pelaksanaan dilakukan melalui survei awal untuk pemetaan kebutuhan, penyusunan materi, sosialisasi literasi digital, pembuatan akun media sosial, serta pendampingan pembuatan konten promosi. Hasil kegiatan menunjukkan bahwa mitra mulai memahami fungsi media sosial dan e-commerce, memiliki akun resmi untuk promosi, serta mampu menghasilkan konten sederhana secara mandiri. Simpulan dari kegiatan ini adalah peningkatan kapasitas digital KWT Gemilang II menjadi fondasi dalam pengelolaan pemasaran berbasis online yang lebih berkelanjutan, sekaligus mendukung pengembangan ekonomi lokal berbasis pangan alternatif.. Kata kunci: digital marketing; kewirausahaan; KWT Gemilang II; MOCAF; UMKM